1986
DOI: 10.1002/j.1460-2075.1986.tb04324.x
|View full text |Cite
|
Sign up to set email alerts
|

Conserved TAAAT motif in vaccinia virus late promoters: overlapping TATA box and site of transcription initiation.

Abstract: We have characterized the vaccinia virus 11‐kd late promoter through 5′ and 3′ deletions and site‐directed mutagenesis. The promoter function appears to be contained within an approximately 30‐bp fragment, which after translocation is able to direct RNA synthesis late in infection at a reduced level. We demonstrate that a TAAAT sequence in the proximal part of the promoter is essential for its function. This cis‐acting element is highly conserved within vaccinia virus late promoters and overlaps the site of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 21 publications
6
80
0
Order By: Relevance
“…We have extended the cluster to include the initiation codon for FPI and another closely packed gene FP0. Both FP0 and FPI appear to be late genes, judged by analysis of their 5' non-coding sequences, which conform to the consensus sequence AA AA TrTAAAToo recently determined for vaccinia virus late genes (Hanggi et al, 1986). The 5' non-coding sequences of FP2, FP3, FP4, FP5, FP6 and FP7 also conform to the consensus although a C residue is present at position 2 in FP5 and FP6, and at position 9 in FP3 (see Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…We have extended the cluster to include the initiation codon for FPI and another closely packed gene FP0. Both FP0 and FPI appear to be late genes, judged by analysis of their 5' non-coding sequences, which conform to the consensus sequence AA AA TrTAAAToo recently determined for vaccinia virus late genes (Hanggi et al, 1986). The 5' non-coding sequences of FP2, FP3, FP4, FP5, FP6 and FP7 also conform to the consensus although a C residue is present at position 2 in FP5 and FP6, and at position 9 in FP3 (see Fig.…”
Section: Discussionsupporting
confidence: 53%
“…In vaccinia virus this conserved region encodes a set of mainly late genes (Plucienniczak et al, 1985) and many of the FPV sequences 5' to the ORFs closely resemble the consensus sequence AA AA rr TAAAT~ which has been proposed for vaccinia virus late promoters (Hanggi et al, 1986). A comparison of the probable promoter sequences present 5' to the genes in FPV and vaccinia virus is presented in Fig.…”
Section: Identification Of the Conserved Regionmentioning
confidence: 77%
See 1 more Smart Citation
“…An 11 bp sequence, GAAAATATATT, has been found upstream of the gene, and is also upstream of the vaccinia virus 7-5K gene (Pickup et al, 1986;Venkatesan et al, 1981). The vaccinia virus 42K K1 gene also appears to be an early gene, in that it does not have the characteristic late TAAAT motif (Hanggi et al, 1986;Rosel et al, 1986) immediately before the ATG codon, and has a potential early TTTTTAT termination of transcription signal (Rohrmann et al, 1986) 78 bases downstream from the termination codon. However, it does not share any sequence homology with sequences upstream of the 7.5K gene.…”
Section: Discussionmentioning
confidence: 99%
“…The fowlpox virus D10, Dll, D12, D13 and A1 genes all have sequences closely related to the consensus a' a" TAAATGG determined for vaccinia virus sequence AA AA late promoters (Hanggi et al, 1986) in a position close to or including their ATG translation initiation codons. Recently it was found that the vaccinia virus DNA ligase gene, which also possesses a consensus late promoter sequence in this position, is predominantly transcribed early during infection , with the 5' end of the mRNA mapping within the late consensus sequence.…”
Section: M Binns and Othersmentioning
confidence: 86%